The effect of feeding cottonseed cake, sesbania or leucaena with crushed maize as supplement to teff straw - Bonsi, M.L.K.; Osuji, P.O. (Elsevier, 1997)
This study was aimed at determining the effects of feeding an energy source on nitrogen utilization by Ethiopian Menz rams. Intake, digestibility, teff straw degradation, rumen pH and ammonia-nitrogen, nitrogen balance and purine derivatives were measured in the digestibility and nylon bag studies. All experimental sheep were offered teff straw basal diet ad libitum (unrestricted). With the exception of sheep fed the control diet, others received diets supplemented with either cottonseed cake (19.56), sundried sesbania and sundried leucaena (22 g dry matter kg to the square root of -0.75 weight day to the square root of -1) in addition to 45.5 g dry matter head to the square root of -1 day to the square root of -1 crushed maize. The supplemented diets improved (P<0.05) the dry and organic matter intake of teff straw, total feed intakes and digestibilities, nitrogen utilization, microbial protein synthesis, the rumen pH and ammonia nitrogen. While the intakes of teff straw and total feed were higher (P<0.05) for sheep fed the foliage than cottonseed cake diets, the opposite trend was recorded for nitrogen balance. Total purine derivatives and microbial N values were however similar (P>0.05). Cottonseed cake and sesbania seem to combine better with maize in terms of roughahge intake and nitrogen utilization, respectively than with leucaena. The need to feed supplemented diets to ruminants was confirmed in this study.